Addressing the incremental risks associated with adopting a Bring Your Own Device program by using the COBIT 5 framework to identify keycontrols - Weber, Lyle (Stellenbosch : Stellenbosch University, 2014)
Thesis (MComm)--Stellenbosch University, 2014.